IMPLEMENTATION OF QURANIC LITERACY IN FORMING STUDENTS' DISCIPLINE CHARACTER - Taufiq Akbar, Imam; Winoto, Suhadi; Umam, Khotibul (Nurul Jadid University, Paiton Probolinggo, East Java, 2023)
Character education is a character that is centered on individual learners as a foundation in thinking, acting and behaving. So it is very important to instill a disciplined character through Qur'anic literacy. This research methodology uses qualitative research case studies. Data collection techniques were obtained from primary and secondary sources both from field observations and digital literature. The results of the research obtained that Qur'anic literacy had a close relationship with the formation of the disciplinary character of students in MTs Mabdaul Ma'arif. Meanwhile, from the planning aspect, it has been neatly structured from the schedule of activities, the selection of coaches, supervision carried out by student guardians, and adequate infrastructure. Then evaluated by holding a dialogue between students and teachers or coaches that produce appropriated guidelines in the development of Quranic literacy in the MTs Mabdaul Ma'arif environment.